Technical Feasibility Analysis of Processing Food Waste into Organic Fertilizer with Black Soldier Fly Composting Method - Astuti, Ulvi Pri; Setiani, Vivin; Putri, Anindya Taffana; Hayati, Debby Zintya; Fadilla, Laras Nur; Aviantari, Maura Diza; Setyawati, Emeralda Eka Putri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Food waste is a major issue in Indonesia, accounting for 41.97% of waste generated. This untreated waste can lead to the production of greenhouse gases. However, food waste has the potential to be composted due to its high nutrient content. The purpose of this study was to analyze the technical feasibility of processing food waste using the Black Soldier Fly (BSF) composting method for organic fertilizer production. The study used variations of fish waste and reject milk as composting mixtures, with percentages of 100% food waste, 70% food waste and 30% cow manure, and 30% food waste and 70% fish waste. The dimensions of the BSF composting reactor were 56 cm x 43 cm x 20 cm. The research was conducted for 15 days with the addition of local microorganisms (MoL) to accelerate the degradation process. Various parameters such as pH, moisture content, C-Organic, nitrogen, phosphorus, and potassium were analyzed. The results showed that all variations met the required compost quality standards, it which was technically feasible to be used as organic fertilizer using the BSF composting method. The results of this study can improve the circular economy because compost and bsf larvae products have many benefits if traded.